Whistleblowing for Change : Exposing Systems of Power and Injustice - Bazzichelli, Tatiana (2021)
The courageous acts of whistleblowing that inspired the world over the past few years have changed our perception of surveillance and control in today's information society. But what are the wider effects of whistleblowing as an act of dissent on politics, society, and the arts? How does it contribute to new courses of action, digital tools, and contents? This urgent intervention based on the work of Berlin's Disruption Network Lab examines this growing phenomenon, offering interdisciplinary pathways to empower the public by investigating whistleblowing as a developing political practice that has the ability to provoke change from within.